SOSIALISASI PEMANFAATAN AMPAS TAHU FERMENTASI DALAM RANSUM KAMBING PERANAKAN ETTAWA SEBAGAI UPAYA MENGATASI KEKURANGAN PAKAN PADA MUSIM KEMARAU - Dedhi yustendi; Daniel Daniel; Elvrida Rosa; Sri Fitri; Khumaira Khumaira; Firdaus Firdaus; Muhammad Adham; Firda Mawardah; M. Raihan (Universitas Negeri Medan, 2022)
The socialization of the use of fermented tofu dregs in the ration of the ettawa crossbreed goat as an effort to overcome the lack of feed in the dry season was carried out to the ettawa crossbreed goat breeders in Gp. Emperom District. Jaya Baru Banda Aceh City. This service activity starts from November 27, 2021 until December 2021. The form of this service activity is in the form of socialization and implementation of the use of fermented tofu dregs in dairy goat rations. The objectives of this service activity are; increase knowledge of farmers on the use of tofu dregs as animal feed. The method applied in 2 stages. Phase I, namely providing socialization in the form of; a) Presenting tofu dregs as animal feed ingredients as well as various kinds of raw materials/home industry waste or wastes from processing agricultural products available in Banda Aceh and Aceh Besar cities that can be used as animal feed ingredients. b) Presenting/explaining various kinds of appropriate technological methods to process agricultural waste into animal feed ingredients to farmers and livestock groups. c) Furthermore, breeders are provided with knowledge of the method of formulating feed ingredients into goat rations/concentrates. The outputs obtained by farmers during this service activity are; breeders get an overview of the pattern of giving tofu dregs to livestock properly and correctly starting from; the initial handling, the processing process into raw materials for animal feed, the fermentation method, and the method of formulation into the ration. In addition, farmers are equipped with an understanding of handling agricultural waste by utilizing ammonia and silage technology for ruminant animal feed as an effort to overcome feed shortages in the dry season.